2020
DOI: 10.1080/22221751.2020.1850181
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and epidemiological aspects of non-polio enteroviruses isolated from acute flaccid paralysis in Brazil: a historical series (2005–2017)

Abstract: Due to the advanced stage of polio eradication, the possible role of non-polio enteroviruses (NPEVs) associated to acute flaccid paralysis (AFP) cases has been highlighted. In this study, we described epidemiological aspects of NPEVs infections associated to AFP and explore the viral genetic diversity, information still scarce in Brazil. From 2005 to 2017, 6707 stool samples were collected in the scope of the Brazilian Poliomyelitis Surveillance Program. NPEVs were isolated in 359 samples (5.3%) and 341 (94.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 58 publications
5
31
0
Order By: Relevance
“…Multiple investigations have described the molecular epidemiology of echovirus globally in both clinical and environmental samples [ 13 , 42 , 43 ] including in Brazil [ 16 , 36 ]. Nevertheless, there are limited echovirus nucleotide sequences available in the GenBank database [ 21 , 44 , 45 , 46 , 47 , 48 ], especially full-genome sequences [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Multiple investigations have described the molecular epidemiology of echovirus globally in both clinical and environmental samples [ 13 , 42 , 43 ] including in Brazil [ 16 , 36 ]. Nevertheless, there are limited echovirus nucleotide sequences available in the GenBank database [ 21 , 44 , 45 , 46 , 47 , 48 ], especially full-genome sequences [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that E3 exhibits a distinct epidemic pattern of circulation with regular increases every four to seven years [ 7 , 60 ]. In recent years, E3 has been identified with increased frequency in Brazil, although maintaining its minor pattern of prevalence [ 17 , 46 , 47 , 48 ]. Sequencing methods have become more accessible, and genetic characterization of EV strains is the basis for current EV genotyping [ 60 ], perhaps leading to an increased E3 identification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations